Effect of oligogalacturonides on the biochemical response of tomato under high metal concentrations - Cartaya-Rubio, Omar Enrique (2024)
Introduction. Heavy metal pollution is a growing problem due to human activities. Plants can remove, destroy, or transform contaminants from soil, water, and air. By using plant growth regulators and chelating agents, heavy metal toxicity can be reduced. Objective. To evaluate the effect of applying a mixture of oligogalacturonides on peroxidase activity and the contents of malondialdehyde, total protein, and chlorophylls in tomato plants (Solanum lycopersicum L.) var. Amalia subjected to high levels of heavy metals. Materials and methods. Soil contaminated with Cu, Cd, and Fe was collected from the Adalberto Vidal White Ceramic Company in Mayabeque, Cuba, in 2020. The experiment was conducted in 7 kg capacity bags using tomato plants, under semi-controlled conditions at the Instituto Nacional de Ciencias Agrícolas (INCA), with a completely randomized experimental design with each treatment having ten replicates. The treatments with the oligogalacturonides (Ogal) were soil application (30 mg kg-1); foliar spray (20 mg L-1), the combination of these application forms, and a control. Peroxidase activity and the contents of malondialdehyde, total protein, and chlorophylls were determined at 35 and 56 days after the plant’s emergence. Results. The effect of Cu, Cd, and Fe on the seedlings was attenuated by all the use of the Ogal mixture variants use, indicating that they have developed adaptation mechanisms to high metal concentrations which allows to withstand abiotic stress. Conclusions. The Ogal mixture attenuated the effect of heavy metals on peroxidase activity, malondialdehyde content, total proteins, and chlorophylls in Amalia tomato plants.